2006
DOI: 10.1080/09593332608618690
|View full text |Cite
|
Sign up to set email alerts
|

Constructed Wetlands and Waste Stabilization Ponds for Small Rural Communities in the United Kingdom: A Comparison of Land Area Requirements, Performance and Costs

Abstract: Land area requirements for secondary subsurface horizontal-flow constructed wetlands (CW) and primary and secondary facultative ponds with either unaerated or aerated rock filters were determined for three levels of effluent quality: that specified in the Urban Waste Water Treatment Directive (UWWTD) (< or = 25 mg filtered BOD l(-1) and < or = 150 mg SS l(-1) for waste stabilization ponds (WSP) effluents, and < or = 25 mg unfiltered BOD l(-1) for CW effluents (mean values); and two common requirements of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…of the proposed systems is the area they require: 4 to 25 times more than a CAS does [27]. Mara [43] state that a CW requires more land and is thus more expensive than a WSP, making the latter a more attractive technology. Next to cost and land use, the performance of the treatment systems need to be taken into consideration.…”
Section: Water Quality Improvement Optionsmentioning
confidence: 99%
“…of the proposed systems is the area they require: 4 to 25 times more than a CAS does [27]. Mara [43] state that a CW requires more land and is thus more expensive than a WSP, making the latter a more attractive technology. Next to cost and land use, the performance of the treatment systems need to be taken into consideration.…”
Section: Water Quality Improvement Optionsmentioning
confidence: 99%
“…They are valued for being more cost-effective than intensive wastewater treatment systems, with minimal operational efforts or financial requirements (Greenway, 2005;Kadlec and Wallace, 2009;Kadlec, 2009). Properly designed and operated CWs are reportedly quite effective at reducing nutrient loads and eliminating microbial and pathogen counts from wastewater (Sundaravadivel and Vigneswaran, 2001;Mara, 2006), and recent studies have described good overall removal of broad ranges of contaminants (Conkle et al, 2008;Hijosa-Valsero et al, 2010;Matamoros and Salvadó, 2012;Ávila et al, 2014;Verlicchi and Zambello, 2014). Nevertheless, as with any technology reports exist of toxic effects in wastewater following CW treatment (Breitholtz et al, 2012), but few apparent studies have investigated the potential for sub-lethal responses in aquatic animals exposed to CW wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Shao, L., et al [86] in adopting the input-output energy approach of system accounting estimated that the energy embodied in treating per m 3 of wastewater and removing per kg BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), SSs (Suspended Solids) and NH 3 -N by a CW is only 6.83%, 17.48%, 13.96%, 22.47% and 9.48% respectively of that by a conventional system. Studies that compare the energy requirement of WSPs and CWs for treating mining wastewater is rare but Mara, D. D. [87] showed that on the basis of land area requirement, capital, operating and maintenance costs, WSPs are to be preferred to SSF (Surface Flow) CW. As CWs perform better in metal removal than WSPs, it can be argued that to obtain a performance equal or better than that of a CW, more energy, land area may be required.…”
Section: Energy Requirementmentioning
confidence: 99%